Phytoplasma diseases of coconut in India - root (wilt) and tatipaka diseases - J.J. Solomon; L. Geetha (International Coconut Community Journal, 2004)
Root (wilt) and Tatipaka diseases in India are caused by phytoplasma. Lethal yellowing disease in Caribbean region, Lethal yellowing like disease in west and east Africa and Coconut stem necrosis.in Sumatra and Peninsular Malaysia are phytoplasma induced diseases of coconut in other continents. Root wilt disease in India was first reported from Kerala in 1874.Tatipaka disease was first noticed in Andhra Pradesh after the 1949 cyclone. The progress made on various aspects including history, nature of spread, description of external & internal symptoms, etiology abiotic factors, biotic agents implicated in transmission of disease, culturing, chemotherapy, screening of coconut germplasm, breeding for disease resistance/tolerance and disease management is detailed.